1963
DOI: 10.1126/science.142.3599.1575
|View full text |Cite
|
Sign up to set email alerts
|

Species Abundance: Natural Regulation of Insular Variation

Abstract: Variation in numbers of land plant species on islands in the Galapagos Archipelago can be predicted on the basis of elevation, area of the adjacent island, distance from the nearest island, and distance from the center of the archipelago, but not on the basis of the area of the host island. Multiple linear regression (y = bx(1) + bx(2) . . .) gives better "goodness of fit" than curvilinear analysis (y = bx(z)). The variation in number of species on large islands can be predicted more accurately than the variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 10 publications
3
49
0
Order By: Relevance
“…These results are in agreement with previous studies, which demonstrated that island area and highest elevation are both important predictors for plant diversity on remote islands (Ackerman et al, 2007;Hamilton et al, 1963;Johnson & Raven, 1973;McMaster, 2005). Largest and highest islands harbor more habitat diversity and tend to contain more native species, and vice versa.…”
Section: Physical Geography 507supporting
confidence: 95%
See 1 more Smart Citation
“…These results are in agreement with previous studies, which demonstrated that island area and highest elevation are both important predictors for plant diversity on remote islands (Ackerman et al, 2007;Hamilton et al, 1963;Johnson & Raven, 1973;McMaster, 2005). Largest and highest islands harbor more habitat diversity and tend to contain more native species, and vice versa.…”
Section: Physical Geography 507supporting
confidence: 95%
“…For example, Hamilton, Rubinoff, Barth, and Bush (1963) and Johnson and Raven (1973) concluded that elevation is significant for plant diversity in the Galapagos Archipelago. On the islands of the northeast coast of Australia, Buckley (1985) showed the influence of both elevation and substrate type on plant diversity.…”
Section: Introductionmentioning
confidence: 97%
“…Ackerman et al, 2007;Diamond, 1975;Paulay, 1994;Preston, 1962aPreston, , 1962bRosenzweig, 1995). For example, Hamilton et al (1963) and Johnson and Raven (1973) reported that elevation was significant for native plant species richness and diversity in the Galapagos Archipelago and similar results were obtained on the tropical islands of the northeast coast of Australia (Buckley, 1985), West Indies (McMaster, 2005) and French Polynesia (Larrue, 2014). In addition, edaphic substrata, soil nutrients, climate and productivity (see species-energy theory) also influence species richness on the islands (Field et al, 2008;John et al, 2007;Kalmar and Currie, 2006;Wright, 1983).…”
Section: Introductionsupporting
confidence: 62%
“…It is now more or less accepted that the area of the islands per se does not explain all the variation in species number. Thus elevation, number of soil types, substrate types, plant species richness, number of habitats, habitat diversity, structure and heterogeneity have frequently been used to explain the species area curve (see Hamilton et al, 1963;Weissman & Rentz, 1976;Williamson, 1981;Buckley, 1985;Deshaye & Morisset, 1988;Rydin & Borgegard, 1988;Kelly, Wilson & Mark, 1989;Hart & Horwitz, 1991;Becker, 1992). In fact, many factors which could affect either immigration and extinction were not included in the original equilibrium model of MacArthur & Wilson (1963.…”
Section: Introductionmentioning
confidence: 99%